2000
DOI: 10.1007/bf03027306
|View full text |Cite
|
Sign up to set email alerts
|

Emission sources of atmospheric phosphine and simulation of phosphine formation

Abstract: Preliminary results on the emission sources of atmospheric phosphine and the types of its precursors in the environment are described. Sunlight plays a more important role than oxygen in its degradation. The vertical profile of phosphine levels in ambient air has been measured. Laboratory simulation of phosphine formation under anaerobic conditions shows that addition of chicken manure, bone powder, or lecithin leads to an increment in phosphine emission. Phosphine can also be adsorbed to soil matrix and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Several independent reports claim that phosphine can be produced by biochemical processes in the laboratory (Cao et al, 2000;Devai et al, 1984Devai et al, , 1988Eismann et al, 1997;Gassmann and Glindemann, 1993;Iverson, 1968;Jenkins et al, 2000). Most of these results have been summarized in a review (Roels and Verstraete, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several independent reports claim that phosphine can be produced by biochemical processes in the laboratory (Cao et al, 2000;Devai et al, 1984Devai et al, , 1988Eismann et al, 1997;Gassmann and Glindemann, 1993;Iverson, 1968;Jenkins et al, 2000). Most of these results have been summarized in a review (Roels and Verstraete, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…sphere. Cao et al 2000 have studied the possible phosphine formation mechanism in the environment. However, no quantitative information on phosphine emission fluxes from soil has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Rutishauser et al [14] confirmed that inoculation with sterilized sewage sludge or sewage sludge added to a medium supplemented with formaldehyde or mercuric chloride exhibited the complete absence of phosphine after several days of incubation when phosphate was used as the source of phosphorus. Cao et al [28] showed that the release of phosphine from a system that was not sterilized and had added lecithin, was significantly higher than that of the corresponding sterilized system. This indicates that phosphine originated from inorganic or organic phosphorus compounds by microbial activity.…”
Section: Discussion Of the Origin And Fate Of Phosphinementioning
confidence: 99%